Arduino-Based Non-Invasive Blood Sugar Analyzer Instrumentation System - Hariono, Tholib; Fitri, Izzatul Indana (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Arduino-based Non-Invasive Blood Sugar Measurement Instrumentation System is a system designed to measure blood sugar levels without requiring blood samples, as in invasive methods. The system uses photodiodes and LEDs (Light Emitting Diodes) function as a measurement process using optical principles. Arduino as the base of the microcontroller to manage the sensor and measurement process, process the data from the sensor, and send it to the LCD for display. The testing and calibration of the device showed that the average error percentage was around 2.91%, indicating an excellent degree of accuracy in measuring sugar levels non-invasively, although there were slight deviations that were still within acceptable tolerances. By considering the average result of the percentage of error it can be concluded that this system is effective and reliable for blood sugar measurement without invasive.